Increased FLI-1 Expression is Associated With Poor Prognosis in Non–Small Cell Lung Cancers. Issue 8 (September 2016) - Lin, Shiou-Fu; Wu, Chun-Chieh; Chai, Chee-Yin
Abstract : Friend leukemia integration-1 (FLI-1) antibody, a commercially available antibody directed against the C-terminus of FLI-1 protein-binding domain, has been used as a useful tool in the differential diagnosis of small blue round cell tumors and vascular neoplasms, but shows inconsistent expression in lung cancers. The aims of this study were to evaluate FLI-1 immunohistochemical expression in non–small cell lung cancer (NSCLC), and its relationships between the clinicopathologic parameters and prognosis. We investigated the FLI-1 expression in 108 cases of NSCLC by using multiple tumor microarrays. Correlations between the FLI-1 expression and clinicopathologic parameters and prognostic significance were analyzed. The effect of FLI-1 expression on survival is estimated by Kaplan-Meier survival analysis and Cox proportional hazards models. Our results revealed that patients with high FLI-1 expression had shorter overall survival ( P =0.014) than those with low FLI-1 expression. In multivariate analysis, FLI-1 was confirmed as an independent poor prognostic factor in NSCLC (overall survival: hazard ratio, 7.292; 95% confidence interval, 0.294-0.823; P =0.007). In conclusion, this study shows that FLI-1 is expressed variably in different subtypes of NSCLC, and its expression is related to clinicopathologic parameters and poorer prognosis. However, further studies are required to elucidate its function in tumorigenesis of NSCLC.